Treatment of advanced gastric cancer. Controversial aspects / s. - Ruso, Luis; Carrerou, Luis; Montano, Daniel; González, Fernando; Catalá, Gaspar; Gatti, Adriana (Cirugía del Uruguay, 2001)
This working group thanks the authorities of the 50th Uruguayan Congress of Surgery, by the assigned responsibility to address this issue and to who with the contribution of their experience, advice and questions, contributed to shaping this table. The first description of a gastric cancer, corresponds to Avicenna and the first gastric resection to Billroth a little over a century ago.